Modulation of the tumor microenvironment by microbiota-derived short-chain fatty acids: impact in colorectal cancer therapy - Gomes, Sara (2023)
Finding new therapeutic approaches towards colorectal cancer (CRC) is of increased relevance, as CRC is one of the most common cancers worldwide. CRC standard therapy includes surgery, chemotherapy, and radiotherapy, which may be used alone or in combination. The reported side effects and acquired resistance associated with these strategies lead to an increasing need to search for new therapies with better efficacy and less toxicity. Several studies have demonstrated the antitumorigenic properties of microbiota-derived short-chain fatty acids (SCFAs). The tumor microenvironment is composed by non-cellular components, microbiota, and a great diversity of cells, such as immune cells. The influence of SCFAs on the different constituents of the tumor microenvironment is an important issue that should be taken into consideration, and to the best of our knowledge there is a lack of reviews on this subject. The tumor microenvironment is not only closely related to the growth and development of CRC but also affects the treatment and prognosis of the patients. Immunotherapy has emerged as a new hope, but, in CRC, it was found that only a small percentage of patients benefit from this treatment being closely dependent on the genetic background of the tumors. The aim of this review was to perform an up-to-date critical literature review on current knowledge regarding the effects of microbiota-derived SCFAs in the tumor microenvironment, particularly in the context of CRC and its impact in CRC therapeutic strategies. SCFAs, namely acetate, butyrate, and propionate, have the ability to modulate the tumor microenvironment in distinct ways. SCFAs promote immune cell differentiation, downregulate the expression of pro-inflammatory mediators, and restrict the tumor-induced angiogenesis. SCFAs also sustain the integrity of basement membranes and modulate the intestinal pH. CRC patients have lower concentrations of SCFAs than healthy individuals. Increasing the production of SCFAs through the manipulation of the gut microbiota could constitute an important therapeutic strategy towards CRC due to their antitumorigenic effect and ability of modulating tumor microenvironment.